A dual reporter screening system identifies the amino acid at position 82 in Flp site-specific recombinase as a determinant for target specificity - Voziyanov, Yuri (Oxford University Press, 2002)
We have developed a dual reporter screen in Escherichia coli for identifying variants of the Flp site-specific recombinase that have acquired reactivity at an altered target site (mFRT). In one reporter, the lacZα gene segment is flanked by mFRTs in direct orientation. In the other, the red fluorescence protein (RFP) gene is flanked by the native FRTs. Hence, the color of a colony on an X-gal indicator plate indicates the recombination potential of the variant Flp protein expressed in it: blue if no recombination or only FRT recombination occurs, red if only mFRT recombination occurs and white if both FRT and mFRT recombinations occur. The scheme was validated by identification and in vivo characterization of Flp variants that show either relaxed specificity (active on FRT and mFRT) or moderately shifted specificity toward mFRT. We find that alteration of Lys-82 to Met, Thr, Arg or His enables the corresponding Flp variants to recombine FRT sites as well as altered FRT sites containing a substitution of G-C by C-G at position 1 of the Flp binding element (mFRT11). In contrast, wild-type Flp has no detectable activity on mFRT11. When Lys-82 is replaced by Tyr, the resulting Flp variant shows a small but reproducible preference for mFRT11 over FRT. However, this preference for mFRT11 is nearly lost when Tyr-82 is substituted by Phe.